Influences of Motivations, Spatial Characteristics, and Activities on Sense of Place in Bandung Tourist Destinations - Effendi, Qonitah; Subur, Novia Ruslan; Kusuma, Hanson E.; Nugroho, Agung Cahyo (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
Visitor interest in tourist destinations can change, leading to decreased visitation rates. The existence and sustainability of tourist destinations depend on the sense of place. Therefore, this research aims to determine the dimensions of motivations, spatial, physical characteristics, and activities influencing the sense of place in tourist destinations within the Bandung area. The first stage was carried out through exploratory qualitative research using content analysis while the second stage adopted explanatory quantitative research using principal component analysis (PCA) and factor analysis (FA) methods. The first and second stages included 134 and 150 respondents, consisting of both local and interlocal tourists. The analysis showed two dimensions of the sense of place, namely attachment and compatibility. The social activities dimension directly influences attachment. The dimensions of social activities, adventure, photography, and the spatial physical characteristics of beauty directly influence compatibility. The results show that the importance of managing the spatial physical characteristics of tourist destinations can attract individuals’ travel motivations and create activities shaping the sense of place. Strategies implemented include developing tourist destinations that support social activities, creating visually appealing environments to promote photography, and balancing the quality of nature. Effective management of these characteristics can increase visitor numbers and encourage repeat visits, ensuring the existence and sustainability of the tourist destination.